Underpricing of venture-backed and non venture-backed IPOs: Germany's Neuer Markt - Stefanie A. Franzke (Goethe University Frankfurt, Center for Financial Studies (CFS), 2001)
This paper analyzes a comprehensive data set of 108 non venture-backed, 58 venturebacked and 33 bridge financed companies going public at Germany's Neuer Markt between March 1997 and March 2000. I examine whether these three types of issues differ with regard to issuer characteristics, balance sheet data or offering characteristics. Moreover, this empirical study contributes to the underpricing literature by focusing on the complementary or rather competing role of venture capitalists and underwriters in certifying the quality of a company when going public. Companies backed by a prestigious venture capitalist and/or underwritten by a top bank are expected to show less underpricing at the initial public offering (IPO) due to a reduced ex-ante uncertainty. This study provides evidence to the contrary: VCbacked IPOs appear to be more underpriced than non VC-backed IPOs.
urn:nbn:de:hebis:30-10962
Keywords: G32; 330; Venture Capital; Underwriter; Initial Public Offering; Underpricing; Neuer Markt